The Economics of Hosting Refugees : A Host Community Perspective from Turkana - Alix-Garcia, Jennifer; Artuc, Erhan; Onder, Harun (World Bank, Washington, DC, 2017)
In 1991, thousands of South Sudanese boys walked into Kenya. Having fled war in their own countries, about 20 thousand of these "lost boys" first tried taking refuge in Ethiopia. With no real options to stay, many were killed on their walk back to South Sudan or while attempting to swim the crocodile infested River Gilo, before entering Kenya. Between 7 thousand and 10 thousand were estimated to have made it alive to Kenya at that time, with no possessions besides the clothes on their back. The arrival of these "lost boys" eventually transformed how the Kenyan Government approached the issue of refugees. The Government had allowed for the integration of arriving refugees into the Kenyan population up until that point. The arrival of these "lost boys" marked the beginning of the encampment strategy in Kenya. From that point onwards, the refugee screening process was turned over from the Kenyan government to the United Nations High Commission for Refugess (UNHCR) . The boys were initially housed in a temporary camp located closer to the Sudanese border, in the town of Lokichogio. In June of 1002, the camp was relocated farther south to Kakuma Town, in the central Turkana region, where it has remained since. Flash-forward 35 years, with more than 180 thousand refuges, the Kakuma Refugee Camp stands as one of the largest urban settlements on the plains of Turkana. The camp currently houses individuals from different nationalities, primarily Sudanese, Somalis and Ethiopians. There is a significant internal economy of goods and services, bolstered by the goods (especially food) and public services provided by international organizations.